Molecular cloning and nucleotide sequence of the alpha-toxin (phospholipase C) of Clostridium perfringens. - Titball, R W (1989)
A fragment of DNA containing the gene coding for the phospholipase C (alpha-toxin) of Clostridium perfringens was cloned into Escherichia coli. The cloned DNA appeared to code only for the alpha-toxin and contained both the coding region and its associated gene promoter. The nucleotide sequence of the cloned DNA was determined, and an open reading frame was identified which encoded a protein with a molecular weight of 42,528. By comparison of the gene sequence with the N-terminal amino acid sequence of the protein, a 28-amino-acid signal sequence was identified. The gene promoter showed considerable homology with the E. coli sigma 55 consensus promoter sequences, and this may explain why the gene was expressed by E. coli. The cloned gene product appeared to be virtually identical to the native protein. A 77-amino-acid stretch that was close to the N terminus of the alpha-toxin showed considerable homology with similarly located regions of the Bacillus cereus phosphatidylcholine, preferring phospholipase C and weaker homology with the phospholipase C from Pseudomonas aeruginosa.